Functional changes in the human auditory cortex in ageing - Profant, Oliver; Tintěra, Jaroslav; Balogová, Zuzana; Ibrahim, Ibrahim; Jilek, Milan; Syka, Josef (PloS one, 2015)
Hearing loss, presbycusis, is one of the most common sensory declines in the ageing population. Presbycusis is characterised by a deterioration in the processing of temporal sound features as well as a decline in speech perception, thus indicating a possible central component. With the aim to explore the central component of presbycusis, we studied the function of the auditory cortex by functional MRI in two groups of elderly subjects (>65 years) and compared the results with young subjects (<lt;30 years). The elderly group with expressed presbycusis (EP) differed from the elderly group with mild presbycusis (MP) in hearing thresholds measured by pure tone audiometry, presence and amplitudes of transient otoacoustic emissions (TEOAE) and distortion-product oto-acoustic emissions (DPOAE), as well as in speech-understanding under noisy conditions. Acoustically evoked activity (pink noise centered around 350 Hz, 700 Hz, 1.5 kHz, 3 kHz, 8 kHz), recorded by BOLD fMRI from an area centered on Heschl's gyrus, was used to determine age-related changes at the level of the auditory cortex. The fMRI showed only minimal activation in response to the 8 kHz stimulation, despite the fact that all subjects heard the stimulus. Both elderly groups showed greater activation in response to acoustical stimuli in the temporal lobes in comparison with young subjects. In addition, activation in the right temporal lobe was more expressed than in the left temporal lobe in both elderly groups, whereas in the young control subjects (YC) leftward lateralization was present. No statistically significant differences in activation of the auditory cortex were found between the MP and EP groups. The greater extent of cortical activation in elderly subjects in comparison with young subjects, with an asymmetry towards the right side, may serve as a compensatory mechanism for the impaired processing of auditory information appearing as a consequence of ageing.
Keywords: audiometrie slovní; Magnetic Resonance Imaging; magnetická rezonanční tomografie; Auditory Cortex; Humans; Acoustic Impedance Tests; Radiography; Auditory Threshold; lidé středního věku; mapování mozku; radiografie; Audiometry, Pure-Tone; Female; Aged; dospělí; audiometrie čistými tóny; stárnutí; senioři; lidé; Aging; Audiometry, Speech; Brain Mapping; Adult; sluchový práh; ženské pohlaví; Male; Middle Aged; presbyakuze; akustické impedanční testy; mužské pohlaví; Presbycusis; sluchové korové centrum